1998
DOI: 10.4315/0362-028x-61.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the SimPlate™ Total Plate Count Method with Petrifilm™, Redigel™, and Conventional Pour-Plate Methods for Enumerating Aerobic Microorganisms in Foods

Abstract: The SimPlate Total Plate Count (TPC) method, developed by IDEXX Laboratories, Inc., is designed to determine the most probable number of aerobic microorganisms in foods. The 24-h test was compared to the conventional plate count agar (PCA) method, the Petrifilm Aerobic Count plates, and the Redigel Total Count procedure for enumerating microflora in 751 food samples. Results using the SimPlate TPC method were highly correlated (r > or = 0.96) with results from other test methods. Slopes (0.96-0.97) were not si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
6

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 0 publications
1
24
0
6
Order By: Relevance
“…Alguns países como estados Unidos, Canadá, Austrália, Coréia, Portugal, Noruega, itália, entre outros, desenvolveram trabalhos e estudos colaborativos para avaliar a eficiência das placas Petrifilm e de outros métodos rápidos em relação aos métodos convencionais [6,7,8,11,16,19,23,24,29].…”
Section: -Introduçãounclassified
“…Alguns países como estados Unidos, Canadá, Austrália, Coréia, Portugal, Noruega, itália, entre outros, desenvolveram trabalhos e estudos colaborativos para avaliar a eficiência das placas Petrifilm e de outros métodos rápidos em relação aos métodos convencionais [6,7,8,11,16,19,23,24,29].…”
Section: -Introduçãounclassified
“…Simplate TM plates have also been submitted to equivalence studies and good correlation indexes were also reported (3,11,15,22,29,30). The correlation indexes found for Petrifilm TM AC plates for the enumeration of mesophilic microorganisms in pasteurized frozen goat milk, compared with the conventional pour-plate method, and the correlations observed in other studies in the literature are presented in Table 2; those for Simplate TM TPC and pour plates, in Table 3, and those for Petrifilm TM AC and Simplate TM TPC, in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…The culture medium contained various substrates that when metabolized released a fluorescent substance (4). In pasteurized milk, the SimPlate™ TPC showed variations in the fluorescence intensity of the positive wells, causing doubt in the readings and low correlation with the standard MAM counting method (1).…”
Section: Introductionmentioning
confidence: 99%